The measurement of decent work in South Africa: a new attempt at studying quality of work - Mackett, Odile (My University, 2020)
The quality of work is central to the growing inequalities in Africa and the world. Central to concerns about the decline in ‘labour share’ is the notion of decent work. In 1999, the International Labour Organisation coined the term ‘decent work’. The purpose of the Decent Work Agenda was not only to establish a definition of good work which can be used as a yardstick for workers, but also to create unity among workers, governments, and employers. Since the development of the term, numerous studies have been undertaken on the quantifiable aspects of the decent work framework, however, almost each study undertaken on the topic has measured different aspects of decent work or limited its enquiry to certain aspects of the definition of the term. As such, no study has measured decent work in a way which is reproducible without the resources which are required to undertake a survey. The purpose of this study is to construct a decent work index, using an iteration of the South African Labour Force Survey. This is useful firstly to identify measures which currently exist in secondary data and it is secondly beneficial in identifying shortcomings in relation to the use of the Labour Force Survey to measure decent work. Using sub-major (2-digit) occupation groups as units of analysis, the study found that there is an expected pattern around how occupations measure in relation to their degree of ‘decency’, meaning that higher paid professionals tend to have more decent occupations compared to low-skilled workers in elementary occupations. However, the higher up the occupational ladder the occupation is, the lower they score in terms of certain indicators, such as decent working time, and balancing work, family, and personal life. Furthermore, the study finds that occupation groups often score differently when the indicators which make up the decent work index are viewed individually rather than as a composite index. These findings imply that operationalising the idea and practice of decent work to understand and address inequality is no easy matter, but that democratising work to highlight the needs and preferences of workers could be one step in the right direction. At the minimum, it requires some engagement with different aspects of decent work in relation to different occupations. Analytically, a more nuanced conceptualisation of decent work is preferable to simple wage-based approaches often utilised by organisations representing the interests of workers.
A thesis submitted in fulfilment to the degree of Doctor of Philosophy to the Faculty of Commerce, Law and Management, School of Economics & Finance, University of the Witwatersrand
Keywords: Decent work; Labour; Labour market; Labour force survey; UCTD; SDG-8: Decent work and economic growth